Investigating Publics’ Communicative Action in Problem Solving (CAPS) Through Data Science - Sunha Yeo; Joohee Kim; Juwon Kim; Sungahn Ko (Media and Communication, 2025)
This study examined the communicative action in problem solving model through data science-driven approaches to enhance the understanding of online publics’ communication behaviors. Using ChatGPT, the study analyzed YouTube comments from news channels that covered a contentious entertainment issue with multiple related events. The findings indicated that communication behaviors changed over time and manifested in diverse combinations. In addition, the study demonstrated that aware publics in the digital era were not merely passive; rather, they engaged in communication activities similar to active publics. Furthermore, it identified distinct communication behaviors associated with certain types of publics, indicating that public types also evolve dynamically across events. The results suggested that the communicative action in problem solving model served as a valuable framework for examining online communication behaviors in the digital era. Based on these insights, this study offered both academic and practical contributions to the field.